DELHI GHARANA MODERN USAGE AND TRENDS OF THE WESTERN EAGLE OF TABLA INSTRUMENT IN RHYTHM INSTRUMENTS: ताल वाद्यों में तबला वाद्य के पश्चिमी बाज का दिल्ली घराना अधुनातन प्रयोग एवं प्रवृत्तियाँ - Taylor, Sharmila; Anuja (International Journal of Research -GRANTHAALAYAH, 2015)
Rhythm is a very important contribution to music. If seen, the entire music world is absorbed in the rhythm itself. If music does not have a rhythm, then music cannot be imagined. The three genres of music that make up music together. The work of singing, playing, dancing and playing them in the same manner is the rhythm. "Tal is an integral part of music and is also a powerful medium of joy. Taal takes Rasanand to the climax by being used in music as various rhythms. Just as the description of various ragas is found in singing. Similarly, the rhythms of different rhythmic rhythms are also found in the rhythm, the performance of different types of lions such as dugun, tigun, aad, kuad, etc. is shown through the tal. संगीत में ताल का बहुत ही महत्वपूर्ण योगदान है। अगर देखा जाए तो ताल में ही पूरा संगीत जगत समाया हुआ है। अगर संगीत में ताल न हो तो संगीत की कल्पना भी नहीं की जा सकती है। संगीत की वह तीनों विधाएं जिससे मिलकर संगीत बना है। गायन, वादन, नृत्य इनको समान रूप में चलाने का कार्य ताल ही करती है। ‘‘ताल संगीत का अभिन्न अंग होने के साथ ही आनन्दोत्पत्ति का सबल माध्यम भी है। ताल विभिन्न लयकारी के रूप से संगीत में प्रयुक्त होकर रसानन्द को चरमोत्कर्ष पर पहंुचाता है। जिस प्रकार गायन में विभिन्न रागों का वर्णन मिलता है। इसी प्रकार ताल में भी विभिन्न लयकारी वाले तालों का वर्णन मिलता है, कहीं समान कहीं असमान कहीं दुगुन, तिगुन, आड, कुआड आदि भिन्न-भिन्न प्रकार की लयों का प्रदर्शन ताल के माध्यम से दर्शाया जाता है।